2021
DOI: 10.1186/s13071-020-04561-w
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-33 is dispensable for Schistosoma mansoni worm maturation and the maintenance of egg-induced pathology in intestines of infected mice

Abstract: Background Schistosomes are trematode worms that dwell in their definitive host’s blood vessels, where females lay eggs that need to be discharged into the environment with host excreta to maintain their life-cycle. Both worms and eggs require type 2 immunity for their maturation and excretion, respectively. However, the immune molecules that orchestrate such immunity remain unclear. Interleukin (IL)-33 is one of the epithelium-derived cytokines that induce type 2 immunity in tissues. The aim o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
(76 reference statements)
1
9
0
Order By: Relevance
“…21,23,24 Although IL-33 promotes type 2 immune responses in infected mice with S. japonicum while not in infected mice with S. mansoni, it has been associated with liver pathology in both experimental models. [20][21][22] The previously reported kinetics of IL-33 levels and the proportions of Treg and Th17 peak at the 8th week post infection are consistent with the period of immunopathological damage of schistosomiasis japonica. 20,25 However, a link between IL-33, an endogenous mediator of tissue damage and its immunomodulatory armamentarium of Th cells, especially Treg and Th17, has not been further elucidated.…”
Section: Introductionsupporting
confidence: 80%
See 3 more Smart Citations
“…21,23,24 Although IL-33 promotes type 2 immune responses in infected mice with S. japonicum while not in infected mice with S. mansoni, it has been associated with liver pathology in both experimental models. [20][21][22] The previously reported kinetics of IL-33 levels and the proportions of Treg and Th17 peak at the 8th week post infection are consistent with the period of immunopathological damage of schistosomiasis japonica. 20,25 However, a link between IL-33, an endogenous mediator of tissue damage and its immunomodulatory armamentarium of Th cells, especially Treg and Th17, has not been further elucidated.…”
Section: Introductionsupporting
confidence: 80%
“…45 However, the role of IL-33 remains controversial in different schistosomiasis settings. [20][21][22] Therefore, more comprehensive exploration and deeper understanding of the IL-33/ST2 pathway especially in the peak of immunopathology during Schistosoma infection are required. In this work, we compiled evidence that the absence of the IL-33/ST2 axis aggravates the liver immunopathology and fibrosis at the 8th week post S. japonicum infection and the lack of this pathway decreases the percentage and function of Treg, along with upregulating the percentage and function of Th17.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the egg count was significantly reduced in group III in comparison to group IV, although the adult counting showed higher reduction rate in group IV in both couple and total count. This could be explained by the fact that Th2 environment in the prepatent period of schistosomiasis is important for female worm maturation and reproduction [ 43 , 44 ]. In the current work IFN γ level was higher in group III indicating more skewing of the immune response toward Th1 environment, compromising the female worm maturation, fecundity and reproduction.…”
Section: Discussionmentioning
confidence: 99%